Winning or losing a run: The role of technological drivers at stages of development - Ana Urraca Ruiz; Nuria Esther Laguna Molina (Atlantic Review of Economics (ARoEc), 2018)
This article studies the role of technology drivers in catching up at different stages of development. Countries can be at different stages of development when entering in a new catching-up cycle. Thus, the technological drivers of growth [technological capabilities, external spillovers, technological specialization and stability of policies in science and technology] can play different roles to accelerate the rate of growth and change their relative position in the leadership rank (win or lose the run). The empirical results show the building of a 'racing pattern' as countries climb up development stages. At earlier stages, infrastructures and qualification play a major role, while at upper stages, the maintenance of leadership depends on accumlating techno-scientific capabilities to innovate. The article also finds that R&D is crucial at any stage of development, as well as the stability of technology policies.
Keywords: O11; O40; O50; O33; O38; 330; Catching up; Technological Drivers; Growth; Stages of growth; Development; World